Genetic determinants of acenocoumarol and phenprocoumon maintenance dose requirements - Cadamuro, Janne; Dieplinger, Benjamin; Felder, Thomas; Kedenko, Igor; Mueller, Thomas; Haltmayer, Meinhard; Patsch, Wolfgang; Oberkofler, Hannes (European journal of clinical pharmacology, 2010)
Objective The variability in warfarin dose requirement is attributable to genetic and environmental factors. Acenocoumarol (AC) and phenprocoumon (PC) are coumarin derivates widely prescribed in European countries for the prevention and treatment of thromboembolic events. The aim of our study was to investigate the contribution of genes involved in the vitamin K cycle to AC and PC maintenance doses. Methods Common single nucleotide polymorphisms (SNPs) in the genes encoding cytochrome P450 family member 2C9 ( CYP2C9 ), vitamin K epoxide reductase complex subunit 1 ( VKORC1 ), γ-glutamyl carboxylase ( GGCX ), calumenin ( CALU ) and apolipoprotein E ( APOE ) were studied in 206 patients receiving AC or PC. Results Compared to patients with the VKORC1 C1173C genotype, maintenance doses for AC or PC were reduced to 74.6 or 70.2% in heterozygous C1173T subjects and to 48.6 or 48.1% in homozygous T1173T subjects ( P < 0.0001). Furthermore maintenance doses for AC and PC were significantly lower in heterozygous CYP2C9*1*3 , CYP2C9*2*3 , and in CYP2C9*3*3 homozygote individuals compared to homozygous CYP2C9*1*1 subjects ( P = 0.0004 and P = 0.0017, respectively). A multiple regression model including age, sex, last INR, VKORC1 , and CYP2C9 genotypes explained ~50% of the variability in AC/PC dose requirements. CALU genotype combinations showed minor effects on PC dose requirements. No associations with AC or PC dose requirements were observed for sequence substitutions in the GGCX or APOE genes. Conclusion These results reveal that interindividual variability in weekly AC and PC maintenance dose requirement is mainly dependent on the VKORC1 1173C>T and the CYP2C9*3 alleles. VKORC1 and CYP2C9 genotyping might provide helpful information to prevent serious bleeding events in subjects receiving AC or PC.